Study on Metabolic Characteristics in Esophageal Squamous Cell Carcinoma Patients with TCM Differentiation of Deficiency of Fluid and Blood Based on Non Target Metabolomics - ZHANG Yushuang, WU Zhongbing, HUANG Ming, JIA Lei, GAO Shuang, ZHAO Weipeng, LI Jing (Zhongguo quanke yixue)
Background Deficiency of fluid and blood is the main clinical manifestation of middle- and advanced-stage patients with esophageal cancer, but there are few reports about the metabolomic characteristics of esophageal squamous cell carcinoma patients with TCM differentiation of deficiency of fluid and blood. Objective To investigate the metabolomic characteristics of esophageal squamous cell carcinoma patients with TCM differentiation of deficiency of fluid and blood. Methods From April to December 2022, 35 esophageal squamous cell carcinoma patients with TCM differentiation of deficiency of fluid and blood, were selected as the case group in the departments of TCM and Thoracic Surgery, the Fourth Hospital of Hebei Medical University, meanwhile 35 healthy volunteers were selected as the control group. Serum specimens were collected, and metabolomic characteristics was analyzed by ultra performance liquid chromatography-mass spectrometry, and then screened the differential metabolites metabolic pathways. Results A total of 88 differential metabolites with substance secondary matching names were screened out; 5 key metabolic pathways with significant difference and 11 related differential metabolites were further screened out. The 5 key metabolic pathways were β-Alanine metabolism pathway, Sphingolipid metabolism pathway, Linoleic acid metabolism pathway, Glycine, serine and threonine metabolism pathway, and Arachidonic acid metabolism pathway. Of the 11 related differential metabolites, β-Alanine, Phosphatidylcholine, L-homoserine, and L-allothreonine were significantly down-regulated, whereas Carnosine, Linoleic acid, 9, 10-DHOME, Hydroxypyruvic acid, Arachidonic acid, Heparin B3, and Thromboxane B2 were significantly up-regulated. Conclusion There are metabolic pathways with significant difference and related differential metabolites in esophageal squamous cell carcinoma patients with TCM differentiation of deficiency of fluid and blood, which mainly involved in metabolic abnormality of energy, such as amino acids and fatty acids.